The Effect of Giving Tomato Juice on Blood Pressure on Menopause - Yusni Podungge; Fira Puili; Endah Yulianingsih; Sri Sujawaty; Puspita Sukmawaty Rasyid (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2022)
Hypertension is a public health problem that occurs in both developed and developing countries. Health Profile of Gorontalo Province in 2017, hypertension was ranked 13th out of 34 provinces in Indonesia at 30.1%. From the data obtained, hypertension in Gorontalo Regency in 2017 has increased. The aim of the study was to determine the effect of giving tomato juice on blood pressure in menopause patients with hypertension at the Gorontalo Health Center. This study using a pre-experimental design that is one group pretest-posttest. The sample in this study amounted to 22 menopause, the independent variable is tomato juice and dependent variable is blood pressure at menopause. This research using Wilcoxon statistical test and the results of the study showed that the average menopausal blood pressure decreased systolic blood pressure by 10-20 mmHg, amounting to 8 people (36.4%) p value = 0.000 (α = 0.05). Wilcoxon statistic is obtained p value = 0.000(α=0.05) thus H0 is rejected and Ha is accepted. Conclusion: There is a significant effect of tomato juice on blood pressure in menopause.